Shear strength of soft soil reinforced with singular bottom ash column - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; M. H., Mohd Ali (2022)
Structures construct on soft clays are often affected by stability and settle-ment problems due to high compressibility, low shear strength and low per-meability of soft clay which will lead to bearing capacity failure and exces-sive settlement. The soft clay samples had the dimensions of 50 mm diameter and 100 mm in height. The bottom ash column had two (2) different area replacement ratios which were 4% and 9% (10 mm and 15 mm diameters re-spectively) with the bottom ash column penetration ratio of 0.3, 0.7 and 1.0. The results of the unconfined compression test show that there is an im-provement in shear strength of soft kaolin clay when reinforced with bottom ash column. For samples with area replacement ratio 4%, the results show the increment of 25%, 37.5% and 50% at Hc/Hs of 0.3, 0.7 and 1.0, respectively in shear strength. Meanwhile, for samples of 9% area replacement ratio, the shear strength of the soft kaolin clay increased about 14.29, 28.57 and 57.14%, respectively. It can be concluded that by reinforcing the soft clay us-ing singular bottom ash column, the shear strength of the soils increases and become more significant as the area replacement ratios and the column pene-tration ratios increase.